2012
DOI: 10.1152/jn.00296.2012
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to nicotine of neurons of the caudal nucleus of the solitary tract correlates with the neuronal projection target

Abstract: The caudal nucleus of the solitary tract (NTS) is the key integrating center of visceral sensory-motor signaling supporting autonomic homeostasis. Two key projections of this nucleus are the parabrachial nucleus (PbN) and the dorsal motor nucleus of the vagus (DMV). The PbN integrates and relays viscerosensory information primarily to the forebrain, supporting behavioral, emotional, and endocrine responses to visceral events, while the DMV contains parasympathetic preganglionic cholinergic motoneurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(38 citation statements)
references
References 64 publications
8
30
0
Order By: Relevance
“…Gao and Smith 2010;Travagli et al 1991Travagli et al , 2006. In rats, DMV-projecting NTS neurons form the most populous nicotine-responsive group of neurons in the nucleus (Feng et al 2012;Feng and Uteshev 2014). Our data demonstrate that GABAergic NTS neurons in particular act as nicotine-sensitive, second-order viscerosensory neurons and that nicotine enhances synaptic excitation in premotor GABA neurons related to gastric projections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gao and Smith 2010;Travagli et al 1991Travagli et al , 2006. In rats, DMV-projecting NTS neurons form the most populous nicotine-responsive group of neurons in the nucleus (Feng et al 2012;Feng and Uteshev 2014). Our data demonstrate that GABAergic NTS neurons in particular act as nicotine-sensitive, second-order viscerosensory neurons and that nicotine enhances synaptic excitation in premotor GABA neurons related to gastric projections.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that nicotine effects in the NTS are differentially expressed, with neurons projecting to forebrain or parabrachial nucleus (PbN) being unaffected and neurons projecting to vagal motor neurons being excited by nicotinic receptor activation (Feng et al 2012;Feng and Uteshev 2014). To determine whether DMV-projecting, gastric motor-related NTS neurons were affected by nicotine, NTS neurons identified after gastric musculature inoculation with PRV614 were voltage-clamped at Ϫ70 mV in the presence of TTX and mEPSCs were examined for responses to focally applied nicotine.…”
Section: Nicotine Effects On Egfp-labeled Gabaergic Nts Neuronsmentioning
confidence: 99%
See 2 more Smart Citations
“…In all, automating surgeries provides a number of benefits for a modest cost, and as such, is becoming an increasingly popular technique 10,11 . But it is important to recognize that the accuracy of the robot depends on quality machining, proper setup, and proper understanding of how CNC machines operate.…”
Section: Discussionmentioning
confidence: 99%